Effect of Ezetimibe on Insulin Secretion in db/db Diabetic Mice. (17th October 2012) - Zhong, Yong; Wang, Jun; Gu, Ping; Shao, Jiaqing; Lu, Bin; Jiang, Shisen
Abstract : Objective . To investigate the effect of ezetimibe on the insulin secretion in db/db mice. Methods . The db/db diabetic mice aged 8 weeks were randomly assigned into 2 groups and intragastrically treated with ezetimibe or placebo for 6 weeks. The age matched db/m mice served as controls. At the end of experiment, glucose tolerance test was performed and then the pancreas was collected for immunohistochemistry. In addition, in vitro perfusion of pancreatic islets was employed for the detection of insulin secretion in the first phase. Results . In the ezetimibe group, the fasting blood glucose was markedly reduced, and the total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) were significantly lowered when compared with those in the control group (P < 0.05 ). At 120 min after glucose tolerance test, the area under curve in the ezetimibe group was significantly smaller than that in the control group (P < 0.05 ), but the AUC INS 0 − 30 was markedly higher. In vitro perfusion of pancreatic islets revealed the first phase insulin secretion was improved. In addition, the insulin expression in the pancreas in the ezetimibe group was significantly increased as compared to the control group. Conclusion . Ezetimibe can improve glucose tolerance, recover the first phase insulin secretion, and protect the function of β cells in mice.